Pertumbuhan Dan Produksi Kedelai Varietas Anjasmoro Pada Tanah Salin - Usnawiyah Usnawiyah; Delvian Delvian (Faculty of Agriculture, Universitas Malikussaleh, 2019)
Increased soybean production is competing with the extension of the use of agricultural land for non- agricultural needs. Therefore the future expansion of agricultural land can only use marginal lands such as peatlands, wetlands and tidal lands. This paper discusses the growth and production of soybean varieties Anjasmoro in saline environments. Varieties Anjasmoro have total leaf area and the percentage ratio of the canopy which is not significantly different from the other varieties tested except Kipas Merah. In the production of components, seed weight Anjasmoro 100 seeds varieties including higher and statistically the same as the varieties Kipas Putih dan Kipas Merah